The Prodigal Cat - Oke, Janette; Nang Chan Yeema (New York, USA Bethany Backyard, 2000)
Mittens is sure there is no other cat as wonderful as she. She's smart, beautiful, and very proud of herself. So it's no surprise when Mittens decides she can manage just fine on her own.
Keywords: Story Collection